Dielectric performance of Hybrid Carbon Nanotube-Alumina Filled Epoxy Nanocomposites / Muhammad Razlan Zakaria...[et al.] - Zakaria, Muhammad Razlan; Abdul Kudus, Muhammad Helmi; Md Akil, Hazizan; Ahmad Rasyid, Mohd Fadli; Salim, Muhamad Saifuddin; Mohd Thirmizir, Mohd Zharif (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The multi-scale hybridisation of alumina (Al2O3) and carbon nanotubes (CNTs) was synthesised with the use of chemical vapour deposition (CVD). The CNTs were grown directly on the Al2O3 particle by utilising a nickel catalyst while being under an atmosphere of methane. When incorporated into the epoxy matrix, the CNT-Al2O3 hybrid filler provided new opportunity for the development of high performance multifunctional composites. The goal of hybridizing CNTs and Al2O3 particles is to avoid CNT agglomeration as a result of van der Waals attractions. The particles of Al2O3 serve as “vehicles” for CNTs so that they can homogenously disperse in the epoxy matrix. As a comparative study, preparation of CNT-Al2O3 was also done through a physical mixing method. The result revealed that compared to the CNT–Al2O3 filler that was physically mixed, the CNT–Al2O3 hybrid filler exhibited a more homogeneous dispersion within the epoxy matrix and it had a higher dielectric constant. Furthermore, compared to the neat epoxy, the dielectric constant of the CNT–Al2O3 hybrid epoxy nanocomposites was enhanced by up to 22%.